Characterization of the intestinal microorganism in patients with congenital intestinal atresia: the preliminary exploration for establishment and influence of initial intestinal flora in newborns - Yang Chen; Ling Zhou; Qianghui Liao; Dong Xiao; Ledao Zhu; Jinlong Yao; Jiashu Liu; Xu’ning Zhang; Xiaopeng Ma; Feng Ren; Zhiyong Wang (BMC Microbiology)
Abstract Purpose This study aimed to analyze the differences in microbial composition between the proximal and distal intestinal segments of newborns with intestinal atresia, speculating about the mechanism underlying the initial establishment of neonatal intestinal flora. Additionally, differential metabolic pathways were explored to predict their potential effects on gravidas and fetuses. Methods The microbial characteristics of intestinal flora were assessed using 16SrRNA sequencing. The alpha and beta-diversity indices were calculated to compare the microbial composition among three groups. Principal Coordinates Analysis (PCoA) was employed to identify and quantify differences in microbial communities. Furthermore, PICRUSt software was utilized to predict the possible functional impacts of differential metabolic pathways by comparing them with public databases. Results Samples were collected from 23 neonates with intestinal atresia (proximal and distal segments) and 25 healthy neonates (first meconium) based on predefined selection criteria. No significant differences in baseline characteristics were observed between the control and intestinal atresia groups (P > 0.05). Alpha-Diversity analysis revealed that the distal intestinal group exhibited greater microbial species richness. Beta-Diversity analysis indicated significant differences in bacterial composition between the control group and the distal intestinal group (P < 0.05), with the distal group showing a more pronounced divergence compared to the proximal group. Functional prediction analysis suggested that the differential metabolic pathways might protect the intestinal mucosal barrier. However, they could also negatively impact blood glucose regulation and lipid transport in gravidas and fetuses, potentially contributing to adverse emotional states in pregnant women. Conclusion The distinct microbial profiles observed among the three groups suggest that the establishment of neonatal intestinal flora may result from a combination of placental transmission and digestive tract colonization. Functional pathway analysis suggested these microbial metabolic differences may exert pleiotropic effects, demonstrating both protective roles in intestinal barrier function and potentially detrimental impacts on emotional modulation and glucose/lipid dysregulation.